2018
DOI: 10.1038/s41467-018-04041-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen minimum zone cryptic sulfur cycling sustained by offshore transport of key sulfur oxidizing bacteria

Abstract: Members of the gammaproteobacterial clade SUP05 couple water column sulfide oxidation to nitrate reduction in sulfidic oxygen minimum zones (OMZs). Their abundance in offshore OMZ waters devoid of detectable sulfide has led to the suggestion that local sulfate reduction fuels SUP05-mediated sulfide oxidation in a so-called “cryptic sulfur cycle”. We examined the distribution and metabolic capacity of SUP05 in Peru Upwelling waters, using a combination of oceanographic, molecular, biogeochemical and single-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
185
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(194 citation statements)
references
References 66 publications
8
185
0
1
Order By: Relevance
“…B). The SUP05 group is already known to transform inorganic sulfur (Marshall and Morris, ; Shah et al ., ; Callbeck et al ., ) and emerges here as a potential contributor to DMSP cleavage. A second exception is the dddP reads placing to the ‘other Alphaproteobacteria’ cluster containing reference genomes from the Rhizobiales.…”
Section: Resultsmentioning
confidence: 73%
“…B). The SUP05 group is already known to transform inorganic sulfur (Marshall and Morris, ; Shah et al ., ; Callbeck et al ., ) and emerges here as a potential contributor to DMSP cleavage. A second exception is the dddP reads placing to the ‘other Alphaproteobacteria’ cluster containing reference genomes from the Rhizobiales.…”
Section: Resultsmentioning
confidence: 73%
“…These clades, besides there potential role for N 2 fixation are a first evidence for a euxinic state of the Peruvian OMZ. So far, there were two recent descriptions of this area developing sulfidic anoxia (Callbeck et al 2018;Schunck et al 2013), however, historical reports of Peruvian fishermen on the characteristic smell and black fishing gear , and at least two earlier descriptions of sulfidic anoxia in those waters point towards a re-occurring sulfidic anoxia in this region (Burtt 1852;Dugdale et al 1977). While the presence of indicator species for euxinia is a curious fact, and their presence in the N 2 fixer pool may be important in a future with intensifying, expanding OMZs and more frequent events of sulfidic anoxia as predicted for other waters (Lennartz et al 2014), only the detection of Chlorobium-nif transcripts points towards an involvement in N 2 fixation.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen minimum zone (OMZ) off Peru is one of the most prominent examples for expanding and progressing deoxygenation challenging the present ecosystem (Stramma et al 2010). On the Peruvian shelf, anoxic conditions are severe, with locally occurring sulfidic events promoting a microbial community very different from other parts of the OMZ (Callbeck et al 2018;Löscher et al 2015;Schunck et al 2013). Here, the water column is Fe-rich (Löscher et al 2014), and anoxic close to the surface, thus sustaining almost euxinic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Vertical and lateral transport processes are believed to be important in shaping the activity and distribution of chemolithoautotrophs in marine oxygen minimum zones. Accordingly, several studies have reported a stimulation of chemolithoautotrophic reactions or transcription of the involved proteins that were induced by such transport processes followed by the mixing of oxygenated and anoxic water bodies (Fuchsman et al ., ; Schmale et al ., ; Callbeck et al ., ; ). On the other hand, the activities of microorganisms unable to utilize and tolerate sulfide may be inhibited after mixing processes in euxinic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Key players in pelagic redoxclines belong to globally distributed groups in oxygen minimum zones which conduct distinct transformation processes (Wright et al, 2012). For example, representatives of the genus Sulfurimonas within the Campylobacteria and the gammaproteobacterial SUP05 cluster couple sulfur oxidation with autotrophic denitrification and are responsible for the high carbon fixation rates at the oxic-anoxic interface (Walsh et al, 2009;Grote et al, 2012;Glaubitz et al, 2013;Shah et al, 2017;Callbeck et al, 2018). Other key players that were shown to mediate ammonium oxidation in the nitrogenous zone are dominated by Crenarchaeota related to Cand.…”
Section: Introductionmentioning
confidence: 99%